TABATTUL MENURUT IBN HAZM (W. 456 H) DALAM PERSPEKTIF HUKUM KELUARGA ISLAM (AL-AHWAL AL-SYAKHSIYAH) - Mara Ongku Hasibuan (AL-FIKRA, 2020)
Getting married is the Prophet's recommendation to his people by getting married to live in peace and even marriage creates a good society (al-mujtami 'al-shālih), the importance of having a family on the one hand because humans cannot live alone because humans are social beings both in social life and family life through marriage. Ibn Hazm  is firm in his opinion that it is mandatory to marry on the condition that if he is able to have a relationship with husband and wife and needs a living. The results of this study explain that the opinion  Ibn Hazm about tabattul haram, according to him, is because it is contradictory to the hadith  the Prophet which advocates marriage and prohibits the tabattul attitude. Ibn Hazm argues that the word sayyida wa hasūrā (to follow and restrain lust), there is no argumentation about the word, because we are not commanded to refrain (lust) from having a household. So according to him, marriage is mandatory provided that you have ability to intercourse with women and the costs of marriage, and it is haram to do tabattul based on the orders of Allah and the Prophet, the existence of sighat orders (amr) and prohibitions (nahy) indicates obligation and prohibition of actions. The commands and prohibitions contained in the Qur’an and hadith according to Ibn Hazm must be understood linguistically because the method used by Ibn Hazm regarding the haram of tabattul is the ijtihad bayani method, which is understanding the law with linguistic ijtihad.